Extreme bilateral polydactyly in a wild‐caught western grey kangaroo. Issue 7 (16th October 2020) - Warburton, Natalie M.; Cake, Martin A.; Kelman, Khama R.
Abstract: Polydactyly is a congenital malformation resulting from an autosomal dominant mutation manifesting as supernumerary digits of the hands or feet. It is most commonly reported in humans and domestic mammals, though there have also been isolated examples across a range of wild vertebrate species. Here we report a case of extremely unusual bilateral preaxial polydactyly on the pectoral limbs of a male western grey kangaroo ( Macropus fuliginosus ) from the South West region of Western Australia, in which two supernumerary digits were present on each manus. A supernumerary digit I on each manus was rudimentary in morphology without extrinsic muscular connections. However, supernumerary digit II present on each manus had fully developed extrinsic and intrinsic muscular connections, suggesting that these digits possessed normal function in flexion and extension. An alternative hypothesis is that the two supernumerary digits are both representatives of the most radial digit I, though this would then require the true digit I to have taken on the appearance of digit II by acquiring an additional phalanx and modified muscular attachments. The carpal bones exhibited a number of subtle differences in morphology when compared to normal pentadactyl individuals. The presence of a distal, rather than proximal, epiphysis on the first metacarpal was unexpected but further investigation suggested that this characteristic is perhaps more variable (in this species at least) than has been previously recognized. This case provides an unusual example to be considered within the broader context of limb development.